2020
DOI: 10.1080/00275514.2020.1785197
|View full text |Cite
|
Sign up to set email alerts
|

Hymenophore configuration of the oak mazegill (Daedalea quercina)

Abstract: The complex hymenophore configuration of the oak mazegill (Daedalea quercina, Polyporales) is rarely quantified, although quantifications are important analytical tools to assess form and growth. We quantified the hymenophore configuration of the oak mazegill by manual counting of tubes and tubular branches and ends. Complementary measurements were made with the software AngioTool. We found that the number of tubular branches and ends varied substantially between specimens, with a positive correlation with hym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…We have previously observed that basidiocarps that are flipped will grow a new hymenophore through the old pileus (Jensen et al 2020 Mycologia). Here, we made observations on nine basidiocarps from three fallen trunk lying on the ground (Flipped trunk natural 1, N=5; Flipped trunk natural 2, N=3; Flipped trunk natural 3, N=1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously observed that basidiocarps that are flipped will grow a new hymenophore through the old pileus (Jensen et al 2020 Mycologia). Here, we made observations on nine basidiocarps from three fallen trunk lying on the ground (Flipped trunk natural 1, N=5; Flipped trunk natural 2, N=3; Flipped trunk natural 3, N=1).…”
Section: Methodsmentioning
confidence: 99%
“…While this may be a trivial observation, it begs the question whether only the margin can configure the hymenophore. Because the hymenophore has an essential constant configuration at any part of its depth (Ames 1913 Jensen et al 2020), it could be concluded the pore field patterns a fixed configuration.…”
Section: Introductionmentioning
confidence: 99%